Ação mediada em aulas de Biologia : um enfoque a partir dos conceitos de fotossíntese e respiração celular - Trazzi, Patricia Silveira da Silva (2015)
This research aimed to investigate the role of mediated action in the configuration of the senses that go through a discursive interaction process in a biology classroom at 1st high school grade in a state public school of the city of Vitória - ES during classes aimed at addressing the photosynthesis and cellular respiration concepts. And for that we start from the idea that the action mediated qualified as organized, dialogic, comprehensive and interactive favors the formation of these scientific concepts for high school students. For that purpose, we started from a theoretical-methodological perspective rooted in a historical and cultural matrix. Collaborative critical action research was used as a methodological approach and the data collection instruments were based on observations of daily school routine and the classroom with records in field diaries, recording of classes using video, questionnaires, written exams from the students and reflective interviews. Data analyzes were based on micro genetic analysis proposed by Vigotski, complemented by a comprehensive analysis anchored in Bakhtin's ideas. Two main angles of analysis were defined: 1 - action mediated in working with students; 2 - statements and meanings produced by the teacher during the research process. The results show evidence that the action mediated described as organized, dialogic, comprehensive and interactive favors the formation of scientific concepts of photosynthesis and cellular respiration by high school students promoting a fruitful teaching as advocated by Vigotski. The results also indicate that the process of collaborative critical-action research showed positive results with regard to the process of continued education for the biology teacher. We conclude that is made necessary investments in teacher training programs, to articulate school and university, integrating initial and continued education for the teachers. For this, we argue that this process of training is done within a critical and collaborative approach based on a mediated action to promote the development of a fruitful teaching